“It was a joke”: On Zinaida Gippius’ scandalous publication in “Severnye tsvety” - Yulia Rykunina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The paper deals with historic and literary case related to Z.N. Gippius’s short story “Mass (Decal)”, its publication and response in press and epistolary documents. The paper presents reviews to it, among them little-known and gives the literary and cultural context of the publication. The author presents her hypothesis about Gippius’s revaluation of her short story in later period.